Acne scars in 18-year-old male adolescents: a population-based study of prevalence and associated factors - Fernanda Tcatch Lauermann; Hiram Larangeira de Almeida Jr; Rodrigo Pereira Duquia; Paulo Ricardo Martins de Souza; Juliano de Avelar Breunig (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Background: Acne vulgaris is a pilosebaceous follicle disorder affecting over 85% of adolescents to some degree. It frequently causes psychological distress that may persist into adulthood due to scarring. Little information about post-acne scarring epidemiology is available. Objectives: To describe prevalence, distribution patterns and associated factors of acne scarring in young males, drawing on a representative population sample from a southern Brazilian city. Methods: A cross-sectional study was undertaken during presentation for military service, which is compulsory for all 18-year-old males. A questionnaire was applied, covering topics like diet, smoking habits, ethnicity, family structure, socio-economic level, as well as specific questions about active acne and resulting scars. Dermatologists conducted the clinical examination. Results: A total of 2,201 male adolescents were interviewed and examined. The overall prevalence of acne scarring was 22%. The malar region was the most frequently involved, present in 80% of affected individuals, followed by the frontal region (31.5%), back (17%), anterior chest (8.2%) and mentonian region (6.4%). Correlation between the intensity of clinical acne and the presence of scars was found, but no association was observed with educational level, smoking, ethnicity, obesity or socio-economic status. Conclusions: There is a high prevalence of acne scars among this population. This is the first study to ascertain a correlation between acne scarring and factors such as socio-economic status and educational level. The direct relation between acne severity and scarring indicates that prompt and effective treatment is the best way to reduce scarring.